(2,2 `-Bipyridine-kappa N-2,N `)bis(N-ethyl-N-methyldithiocarbamato-kappa S-2,S `)zinc(II) - Ghafar, N.A.A.; Baba, I.; Yamin, B.M.; Ng, S.W. (International Union of Crystallography, 2010)
The complete molecule of the title compound, [Zn(C4H8NS2)(2)(C10H8N2)], is generated by crystallographic twofold symmetry, with the Zn atom lying on the rotation axis; the axis also bisects the central C-C bond of the 2,2'-bipyridine molecule. The metal atom is chelated by two S,S'-bidentate dithiocarbamate anions and the N,N'-bidentate heterocycle, resulting in a distorted cis-ZnN2S4 octahedral geometry. The methyl and ethyl groups of the anion are statistically disordered.